THE QUEUE TRANSIENT PROBABILITIES - Ferreira, Manuel Alberto M. (Acta Scientiae et Intellectus, 2024)
In the theory and applications of queuing systems, transient probabilities play a key role. Often, due to the difficulty of their calculation they are replaced by the stationary probabilities. In the case of systems, those calculations are much friendlier than usual. We present in this work formulas for the transient probabilities of the system, where are considered service times with exponential distribution, showing that it is also possible to calculate them with initial conditions different from those usually considered.